Analysing the daily, weekly and yearly cycles of births and their implications for the NHS using linked data. (2017) - Harper, Gill; MacFarlane, Alison; Dattani, Nirupa; Dodwell, Miranda; Gibson, Rod; Cortina, Mario; Martin, Peter
No abstract available